Characterization of the blood pressure response during cycle ergometer cardiopulmonary exercise testing in black and white men : Data from the Fitness Registry and Importance of Exercise: A National Database (FRIEND) - Sabbahi, Ahmad; Arena, Ross; Kaminsky, Leonard A; Myers, Jonathan; Fernhall, Bo; Sundeep, Chaudhry; Phillips, Shane A (Journal of human hypertension, 2021)
It has been established that blacks have higher overall incidence and prevalence of hypertension compared to their white counterparts. However, the maximum blood pressure (BP) response of blacks to exercise has not been characterized. A total of 5996 apparently healthy men from the Fitness Registry and Importance of Exercise: A National Database (FRIEND) who underwent maximum cardiopulmonary exercise tests on a cycle ergometer were included in this analysis. Of these participants, 1245 (21%) self-identified as black while the remaining 4751 (79%) identified as white. All subjects had a respiratory exchange ratio (RER) of ≥1.0 and had no reports of cardiovascular or pulmonary disease. Systolic BP (BP) response to exercise was indexed according to increase in workload (SBP/MET-slope). Both racial groups were subdivided into age groups by decade. Black men had higher peak SBP and higher SBP/MET-slopes compared to white men across all age groups (p < 0.001). Resting SBP was not different between blacks and whites except within the 18-29-year age group. The differences in peak SBP and SBP/MET-slope between age and race groups indicate that black men have an exaggerated BP response to exercise irrespective of resting BP values. Further investigation is warranted to determine the underlying mechanisms responsible and clinical implications for this exaggerated BP response to exercise.